2017
DOI: 10.1088/1367-2630/aa936c
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of ‘waveguide’ plasmonics

Abstract: Surface plasmons polaritons are collective excitations of an electron gas that occur at an interface between negative-ε and positive-ε media. Here, we report the experimental observation of such surface waves using simple waveguide metamaterials filled only with available positive-ε media at microwave frequencies. In contrast to optical designs, in our setup the propagation length of the surface plasmons can be rather long as low loss conventional dielectrics are chosen to avoid typical losses from negative-ε … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Owing to the small size of the constituent unit cells of metamaterials (when compared to the operating wavelength), some aspects of effective medium theory can be utilized to describe the electromagnetic wave propagation inside them. Metamaterials research has opened the door towards the design of artificial media with exotic values of permittivity (ε) and permeability (μ) by properly engineering the geometry, materials and arrangement of the unit cells [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the small size of the constituent unit cells of metamaterials (when compared to the operating wavelength), some aspects of effective medium theory can be utilized to describe the electromagnetic wave propagation inside them. Metamaterials research has opened the door towards the design of artificial media with exotic values of permittivity (ε) and permeability (μ) by properly engineering the geometry, materials and arrangement of the unit cells [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the resonance properties of these modes rely heavily on the geometry (e.g., the groove depth) of the structure, making many interesting properties of natural LSPs still elusive at low frequencies. Alternatively, it has been shown that low‐frequency plasmonics can also be realized with structured dispersion in bounded waveguides . Recently, in a couple of scenarios, this approach has been successfully applied to mimic propagating SPPs exhibiting spatial decay on both sides of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel “natural” SPP-like concept in microwave regime has been proposed, which is based on exploitation of the well-known structural dispersion of the electromagnetic modes in parallel-plate waveguide structure filled only with materials with positive permittivity 32 , 33 . Namely, if a parallel-plate waveguide is divided into two parts by an array of wires placed along the plane normal to the plates, and if the parts are filled with different materials, then the two parts exhibit effective permittivities of opposite signs in a certain frequency range, which allows for SPP to occur at their interface.…”
Section: Introductionmentioning
confidence: 99%